(untitled) (Al Dzahab, 2024)
Purpose: The study aims to analyze the impact of Shopee features facilities and promotions on the consumer behavior of FEBI Islamic State University Sultan Aji Muhammad Idris Samarinda students to understand to what extent these factors influence student consumption decisions. Design/methodology/approach: The study uses quantitative descriptive research through data collection techniques in online questionnaires using 96 samples obtained using the Slovin formula (5%). Findings: The results of this research show that facility features and promotions simultaneously influence the consumer behavior of UINSI Samarinda students. Partially, the facility features have no influence on the consumer behavior of UINSI Samarinda students. However, the promotion variable has a positive and significant effect on consumer behavior of UINSI Samarinda students. Research implications: Every modification in the promotion shop application will affect the behavior of consumer students.